Investigation of Fire and Explosion Accidents in the Drainage Systems Related to Process Industries - Abd Wahi, Muhammad Aizat (Universiti Teknologi PETRONAS, 2010)
The study of fire and explosion in the process related to oil industries has been a significant scope in the oil and gas business. In this work, oily mixture liquid samples have been taken from PETRONAS Refinery Malacca (PPMSB) drainage system. The aim of the study is to investigate the root causes of the fire incident in the drainage system and to provide engineering approach system to prevent from the likelihood of the similar case recurrence. The result of this study may contribute to minimizing the loss of properties, business and life due to fire or explosion. The liquid samples are first going through distillation process to extract the oil in the liquid. The oily liquid then is analyzed experimentally to indicate the components via Gas Chromatography (GC) as well as the gases that formed when the liquid sample is vaporized. Among the components that have been detected are components from alkane, alkene, arene, alcohol and haloalkane group. The liquid sample contains large numbers of hydrocarbon components (CH-) ranging from C1 to C2s From the GC result, several parameters such as average flash point, vapor pressure, boiling point, heat of vaporization and molecular weight for the mixture can be estimated. The calculated value of average flash point is 88.58°C and the molecular weight of 188.01 g/mol. Average enthalpy of vaporization of the sample is 44.81 kJ/mol, vapor pressure of 0.62 mmHg at 25°C while the sample's boiling point is 232.65°C. The heat of combustion is measured using bomb calorimeter which gives 45.7 kJ/g. These results lead to the determination of several parameters such as ignitability, evaporation rate and flash point of the samples. The parameters are analyzed using GC, bomb calorimeter, hydrocarbon gas detector and closed cup apparatus. Since the first element from alkane group detected in the liquid sample is nonane (C9H2o), the gas sample is suspected to contain alkane ranging from methane (CH4) to octane (CsH1s). From the GC result, it has been found that the gases presences in the sample are ranging between CsH12 and CsHts·